PENGARUH BERMAIN ALAT MUSIK DRUM BAND TERHADAP KETERAMPILAN SOSIAL - Aas Asriliyanti; Alis Triena Permanasari; Laily Rosidah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
Social skills are the ability of children to achieve social maturity in accordance with social demands including the ability with social peers, the ability of themselves, ability for the academic success, ability of children’s to meet the demands of others and social skills. Social skills are very important because humans are social beings who cannot live alone but need others in their lives. The aimsof this research was to determine the effect of playing a drum band musical instrument on social availability of children aged 5-6 years. This research was carried out in kindergartens in Serang Banten sub-district which carried out extracurricular playing drum bands. The method used in this study is quantitative with a survey method with 83 students as a sample. The instrument used in this study is a questionnaire. Quantitative data analysis using Microsoft Excel. The results showed that the average child social skills, was 17.38, showed a significant influence (17.38> 1.658), meaning that there was an influence of playing the drum band musical instrument on the social skills of children aged 5-6 years. Thus, playing a drum band is useful for developing all aspects of child development, one of which is social skills.